Successful Management of Presumed Reactivation of Neospora caninum Following Immunosuppression for Immune Thrombocytopenia in an Adult Doberman - Perrine Henry; Paul Rees; Tyler Morrison; Glynn Woods (Veterinary Medicine and Science)
ABSTRACT A 5‐year old, vaccinated, untravelled and neutered female Doberman with occasional exposure to raw food presented for investigation of severe thrombocytopenia and anaemia. Extensive investigations led to a diagnosis of non‐associative immune thrombocytopenia, with secondary bleeds resulting in anaemia. Management with repeated packed red blood cell transfusions, vincristine (0.02 mg/kg single intravenous injection), prednisolone (50 mg/m2/day) and mycophenolate (10 mg/kg twice daily) allowed normalisation of haematology parameters. Scheduled reassessment 10 days after discharge revealed lethargy, ataxia, wide‐based stance and marked generalised muscle wastage. Platelet count remained normal, but biochemistry was supportive of muscle damage. Neospora caninum antibodies were elevated (indirect fluorescence antibodies > 1600). Rapid tapering of prednisolone alongside clindamycin (20 mg/kg twice daily) allowed a complete recovery. Mycophenolate was slowly tapered and discontinued after 12 weeks, as was antibiotic therapy. This case describes the successful management of a dog with presumed neuromuscular neosporosis, suspected secondary to reactivation of the parasite from immunosuppression, and absence of long‐term complications.